EFFECT OF BETA BLOCKERS ON NOCTURNAL ARRHYTHMIAS AND HEART RATE VARIABILITY IN OBSTRUCTIVE SLEEP APNOEA PATIENTS. (June 2018) - Gironi, F.; Lombardi, C.; Mariani, D.; Castiglioni, P.; Faini, P.; Laccu, I.; Mattaliano, P.; Parati, G.
Abstract : Objective: To explore the effects of BB on nocturnal peri-apnoeic heart rate variability (HRV) and on arrhythmias in OSA patients. Design and method: Arrhythmias and increased cardiovascular V are highly prevalent in patients with obstructive sleep apneas (OSA), possibly resulting in fatal events, as showed by the significant increase of sudden cardiac death and arrhythmias during sleep in OSA patients. Data concerning drug effects on this phenomenon are scarce and the use of beta blockers (BB) has been limited by the concern that they might lead to bradyarrhythmias. However, recent evidence suggests that BB mostly reduce rhythm accelerations with trivial influence on decelerations. We enrolled 166 OSA patients (78 BB-treated and 88 BB-naïve), who performed cardiorespiratory polysomnography (PSG) between 2013 and 2015. Patients on antiarrhythmic therapy were excluded. We analysed PSG-derived ECG traces for the assessment of arrhythmias. Moreover, through an ad hoc developed software, we performed a specific analysis of HRV associated with apnoeic events. We considered HR decelerations occurring during the apnoeic phase and accelerations during the post-apnoeic phase (the first five seconds after the resumption of breathing). Statistical analysis was performed with Mann-Whitney U test. Results: We did not find any difference between BB-treated and BB-naïve groups concerning prevalence of nocturnal arrhythmias. HRV analysis showed a reduction of HR accelerations, expressed as RR length, during post-apnoeic phase in BB group (940.7 ± 121.4msec BB-treated vs 897.8 ± 122.5msec BB-naïve; P = 0.040). Moreover, BB-treated patients showed a smaller delta between HR decelerations/accelerations and mean HR during apnoeic phase (58.5 ± 28.5 vs 74.6 ± 40.2msec; P = 0.010 and75.0 ± 42.4 vs 96.7 ± 55.5msec; P = 0.018, respectively). Finally, the delta between HR accelerations and decelerations was smaller in BB-treated group (133.5 ± 63.8 vs 171.3 ± 87.7msec; P = 0.010). Conclusions: BB therapy does not worsen apnoea-induced HR decelerations nor increase the risk of bradyarrhythmias, while reducing the frequency and magnitude of apnoea-induced HR acceleration. Therefore, our study suggests that BB are safe and possibly advantageous in OSA patients, although further studies are needed to establish if in the long term they may have a role in reducing fatal events.